Emotional work stress reactions of emergency medical technicians involved in transporting out-of-hospital cardiac arrest patients with "do not attempt resuscitation" orders. (April 2022) - Tanabe, Ryo; Hongo, Takashi; Mandai, Yasuhiro; Inaba, Mototaka; Yorifuji, Takashi; Nakao, Atsunori; Elmer, Jonathan; Naito, Hiromichi
Abstract: Background: Emergency medical technicians (EMTs) may be subjected to emotional stress during patient treatment/transport. In Japan, dispatched EMTs must attempt resuscitation in all cases of out-of-hospital cardiac arrest (OHCA), including patients with "do not attempt resuscitation" (DNAR) orders and patients whose families do not support resuscitation. We described the characteristics, prevalence, and outcomes of OHCA/DNAR patients, and aimed to identify factors associated with EMT stress when treating them. Methods: We included OHCA patients transported by EMTs in the city of Okayama from 2015 to 2019. We identified patients with DNAR orders based on emergency medical service (EMS) records, then EMTs completed questionnaires regarding the management of those patients and EMTs' emotions. Results: Among 3079 eligible OHCA patients, 122 patients (4%) had DNAR orders (DNAR group), and 2957 (96%) patients had no DNAR orders (no DNAR group). Based on responses from 243 EMT participants involved in OHCA/DNAR transports, we divided EMTs into high stress (73/243, 30%) and low stress (170/243, 70%) groups. EMTs experienced emotional stress from treating patients with family physician orders to transport (AOR: 4.74, 95% CI: 2.35–9.56) and those for whom prehospital defibrillation was performed (AOR: 20.7, 95% CI: 3.10–137.9). Conclusions: Approximately 30% of EMTs providing resuscitation to OHCA/DNAR patients experienced high levels of stress. Establishment of a prehospital emergency system incorporating physician medical direction and updated guidelines for treating patients with DNAR orders may reduce the psychosocial stress of EMTs.